Neuroimmune responses following joint mobilisation and manipulation in people with persistent neck pain: a protocol for a randomised placebo-controlled trial. Issue 3 (8th March 2022) - Lutke Schipholt, Ivo J; Scholten-Peeters, Gwendolyne; Bontkes, Hetty; Coppieters, Michel W
Abstract : Introduction: Joint mobilisation and manipulation often results in immediate pain relief in people with neck pain. However, the biological mechanisms behind pain relief are largely unknown. There is preliminary evidence that joint mobilisation and manipulation lessens the upregulated neuroimmune responses in people with persistent neck pain. Methods and analysis: This study protocol describes a randomised placebo-controlled trial to investigate whether joint mobilisation and manipulation influence neuroimmune responses in people with persistent neck pain. People with persistent neck pain (N=100) will be allocated, in a randomised and concealed manner, to the experimental or control group (ratio 3:1). Short-term (ie, baseline, immediately after and 2 hours after the intervention) neuroimmune responses will be assessed, such as inflammatory marker concentration following in vitro stimulation of whole blood cells, systemic inflammatory marker concentrations directly from blood samples, phenotypic analysis of peripheral blood mononuclear cells and serum cortisol. Participants assigned to the experimental group (N=75) will receive cervical mobilisations targeting the painful and/or restricted cervical segments and a distraction manipulation of the cervicothoracic junction. Participants assigned to the control group (N=25) will receive a placebo mobilisation and placebo manipulation. Using linear mixed models, the short-term neuroimmune responses will be compared (1) between people in the experimental and control group and (2) within the experimental group, between people who experience a good outcome and those with a poor outcome. Furthermore, the association between the short-term neuroimmune responses and pain relief following joint mobilisation and manipulation will be tested in the experimental group. Ethics and dissemination: This trial is approved by the Medical Ethics Committee of Amsterdam University Medical Centre, location VUmc (Approval number: 2018.181). Trial registration number: NL6575 (trialregister.nl